Reconstruction of a complex anterior abdominal wall defect with autologous tissues - a case report (2011)
Background: The anterior abdominal wall is an important complex composite structure that poses a challenge to the reconstructive surgeon. Defects produced from infection, herniation, tumour extirpation or trauma, are often encountered. Different techniques of reconstruction have been described using autologous tissues and prosthetic materials with varying results, availability and cost implications. The use of totally autologous tissues presents a readily available reconstructive option that has been shown to be associated with a satisfactory outcome and low morbidity. In this report, we describe the use of autologous tissues for the reconstruction of a major abdominal wall defect. Method: This communication describes our experience of the use of purely autologous tissues for a full thickness anterior, abdominal wall defect, presented as a case report. Result: The initial result that was obtained confirms that this is a useful technique with a satisfactory outcome with minimal morbidity. Conclusion: Utilizing purely autologous tissues, avoids most of the complications of the other techniques, is readily available, relatively cost-effective (especially advantageous in the developing country) and is less technically demanding.